2007
DOI: 10.1002/jgm.1115
|View full text |Cite
|
Sign up to set email alerts
|

Development of photoreceptor‐specific promoters and their utility to investigate EIAV lentiviral vector mediated gene transfer to photoreceptors

Abstract: It may be possible to use recombinant EIAV vectors containing photoreceptor-specific promoters to drive therapeutic gene expression to treat a range of retinal degenerative diseases where the photoreceptor cell is the primary disease target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…5,6 OCULAR TRANSDUCTION PROFILES OF LENTIVIRAL VECTORS The transduction properties of HIV-1, (refs 7-24) HIV-2, (ref. 25) SIV, [26][27][28][29] EIAV, 21,[30][31][32][33][34][35] FIV, 24,[36][37][38][39][40][41][42][43] and BIV 44 vectors incorporating a diverse array of envelope pseudotypes and transgene promoters have been evaluated after in vivo and ex vivo delivery in a variety of animal species (Supplementary Tables 1 and 2). Most ocular studies have used vesicular stomatitis virus-G (VSV-G)-pseudotyped vectors incorporating ubiquitous promoters and these are described below unless otherwise stated.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 OCULAR TRANSDUCTION PROFILES OF LENTIVIRAL VECTORS The transduction properties of HIV-1, (refs 7-24) HIV-2, (ref. 25) SIV, [26][27][28][29] EIAV, 21,[30][31][32][33][34][35] FIV, 24,[36][37][38][39][40][41][42][43] and BIV 44 vectors incorporating a diverse array of envelope pseudotypes and transgene promoters have been evaluated after in vivo and ex vivo delivery in a variety of animal species (Supplementary Tables 1 and 2). Most ocular studies have used vesicular stomatitis virus-G (VSV-G)-pseudotyped vectors incorporating ubiquitous promoters and these are described below unless otherwise stated.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed that following SR delivery, LVs transduce the RPE efficiently in rodents (Auricchio et al, 2001;Bainbridge et al, 2001;Duisit et al, 2002;Kachi et al, 2009), but PRs variably and inadequately (Miyoshi et al, 1997;Bemelmans et al, 2005;Balaggan et al, 2006). Notably, PR transduction by LVs is inversely correlated to PR differentiation (Miyoshi et al, 1997;Bainbridge et al, 2001;Pang et al, 2006;Nicoud et al, 2007). Consistent with these observations, the SR delivery of LVs to the adult retina was effective in rodent models of IR caused by mutations in genes expressed in the RPE (Vollrath et al, 2001;Bemelmans et al, 2006), whereas perinatal (Takahashi et al, 1999;Hashimoto et al, 2007;Kong et al, 2008) or in utero (Williams et al, 2006) deliveries were required to treat rodent models that bear mutations in genes expressed in PRs.…”
Section: Efficient Viral Vectors Are Key Elements For Successful Retimentioning
confidence: 99%
“…Attempts to improve neuronal targeting by employing pseudotypes derived from neurotropic viruses, such as rabies-G (Balaggan et al, 2006) or mokola (Bemelmans et al, 2005), have met with little success. Similarly, while photoreceptor-specific promoters have been successfully incorporated into both HIV and EIAV vectors, they effectively limit ectopic expression of the transgene, but do not significantly increase the levels of photoreceptor transduction in the adult retina (Miyoshi et al, 1997;Nicoud et al, 2007). Herein, we employ longitudinal in vivo fluorescence imaging to examine the tropism of a further pseudotype derived from Venezuelan equine encephalitis virus (VEEV-G), a zoonotic virus that causes encephalopathy in various equine species and humans.…”
Section: Introductionmentioning
confidence: 97%